Standardisasi Proses Sterilisasi Rendang pada Koperasi Wanita IKABOGA di Wilayah Kerja Badan Pengawasan Obat dan Makanan (BPOM) Kota Padang - Daimon Syukri; Rini Rini; Adhitya Jessica; Novelina; Purnama Dini Hari; Risa Meuthia Fiana; Deden Dermawan; Rudi Alfiansyah; Aurelia Amaliyah Tarumiyo; Yasmin Azzahra (Warta Pengabdian Andalas, 2024)
Rendang, a Minangkabau speciality, has been recognised as the world's most delicious food and Indonesia's national dish. However, Micro, Small and Medium Enterprises (MSMEs) producing rendang in Padang City face obstacles in meeting the commercial sterile food distribution permit standards, especially the calculation of the F0 value (heat sufficiency number). This service activity aims to foster and assist MSME players related to the sterilisation of commercial rendang products with export-level distribution quality by installing an IoT-based data logger on the retort tool to measure the F0 value in real time. The activity involved a pre-workshop, Focus Group Discussion, data logger installation, sterilisation training, and evaluation. It can be concluded that the measurement of the F0 value in the IKABOGA rendang product sterilisation process shows that the optimal sterilisation time is 40 minutes. This 40-minute sterilisation process can be used as a guide for the implementation of sterilisation by IKABOGA and initial data for fulfilling the requirements for a distribution permit but is sufficient to apply for a product distribution permit because it still requires other supporting data. This community service activity is the first step in developing an IoT-based sterilization process to be developed into a smart retort so that it can become an innovative tool that helps all MSMEs in the product sterilization process and meets the requirements for product distribution permits to a national scale.